Návrh strategie rozvoje malé mobilní kavárny - Cetkovská, Barbora (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Diplomová práce je zaměřena na návrh potenciálního směru dalšího rozvoje rodinné pojízdné kavárny. Teoretická část se zabývá problematikou rozvoje a růstu zaměřenou na malé podniky včetně vybraných analyticko-výzkumných metod zkoumajících vnitřní a vnější okolí podniku. Analytická část obsahuje praktickou aplikaci vybraných analýz a marketingového průzkumu s cílem zajištění dat a informací pro následné rozhodování a výběr vhodné strategie. Navrhovaná část navazuje na zhodnocení výsledků, na základě kterých je vybrána vhodná strategie rozvoje kavárny směřujícímu k lepšímu upevnění pozice na daném trhu. Návrhy jsou zpracovány do podoby implementace navržených akcí včetně zhodnocení přínosů a rizik.

The diploma thesis is focused on the proposal of potential future development of the family coffee truck. The theoretical part handles problematics of development and growth of the small companies including selected analytical and research methods that examine internal and external environment of the company. Analytical part contains the practical application of analytical methods and marketing research in order to find a data and information for future decision and selection of the appropriate strategy. The last part of the thesis is focused on the results of the provided analyzes and recomends the most suitable strategy to strengthen company´s position in the market. The proposals are processed into the implementation of the proposed actions, including an assessment of the benefits and risks.
The Proposal for the Development Strategy of a Small Mobile Coffee Shop
Keywords: strategie rozvoje; živnost; marketingový průzkum; strategická analýza; mobilní kavárna; development strategy; trade; marketing research; strategic analysis; mobile coffee truck